Fracture resistant and wear corrosion performance of CrN/ZrN bilayers deposited onto AISI 420 stainless steel (2008)
CrN/ZrN (1, 8, 15, and 30) bilayers were deposited onto AISI 420 steel substrates at 250°C and 6.6x10-3 mbar with gas ratio Ar/N2 50:3.0 as gas mixture and bias -60V were applied. AFM analysis presented different morphologies, showing that the coatings with 15 bilayers had an average grain size of 49 nm; while the 30-bilayer coating exhibited grain sizes of 99 nm. Coating thicknesses were 3 µm, approximately. The Vickers Test revealed that coatings with 8, 15, and 30 bilayers bore better impact resistance than coatings with 1 bilayer. This result is considered, bearing in mind that in many bilayers propagation of fissures is slower, because the presence of layer inter-phases leads to fissures straying in other directions. Slight corrosion specks are present, but mass loss was around 40 mg. in one bilayer, a higher value than for the coatings with 15 bilayers that was near 18 mg. Homogeneity, grain size, fracture resistance, and corrosion resistance of the coatings with 15 and 30 bilayers are suitable for mechanical applications of these types of coatings, as shown in mechanical measurements. These results indicate that for engineering applications under corrosive environments, the use of these types of bilayer coatings on AISI 420 stainless steel is highly recommended.